Study of the Effects of Regenerative Braking System on a Hybrid Diagnostic Train - Francesco Cutrignelli; Gianmarco Saponaro; Michele Stefanizzi; Marco Torresi; Sergio Mario Camporeale (Energies, 2023)
Nowadays, mobility represents a key sector to achieve the goal of carbon neutrality. Indeed, the development of hybrid powertrains is contributing to a reduction in the environmental impact of vehicles. One of the most promising energy-saving solutions is regenerative braking, which enables deceleration while recovering energy, otherwise wasted. Even though much scientific community effort has been addressed to the optimization of this technology in the automotive field, the increase of energy storage systems efficiencies enables the overcoming of the constraints related to the reuse of electric energy in railway vehicles. This solution could be extremely useful for those railway vehicles which operate on non-electrified lines, where traction is usually provided by diesel engines. For this reason, the present work focuses on how regenerative braking technology could be exploited in diesel-powered rail applications. In further detail, a diagnostic train working on real railway lines has been considered as a case study. Given the real duty-cycle of the vehicle, a simulation model has been developed with the aim of evaluating the amount of energy recovered during braking phases and, consequently, the fuel saving and the avoided CO2 emissions. As a result, the analysis shows an improved energy efficiency of propulsion system. Compared with a pure diesel operation, it leads to fuel savings of 20%, a reduction of CO2 emissions of 22.3 kg with 23.25 kWh stored in the battery at the end of the route.